Free faecal liquid in horses : associations with nutritional factors - Rönnqvist, Elena (SLU/Dept. of Animal Nutrition and Management (until 231231), 2020)
The occurrence of free faecal liquid (FFL) in horses is a problem as it leads to contamination of the tail and inside of hindlegs, which may result in skin lesions. Distinct from diarrhoea, horses with this condition often defecate normal faeces, but also void faecal liquid before, during or after defecation of solid faeces. Anecdotally, feed related factors such as feeding of haylage, silage or increased amounts of lucerne has been suggested to cause FFL. The aim of this study was therefore to compare feeding, feed rations and feeding routines between horses affected by FFL (case group) and horses not affected by FFL (control group). Data on feeding and forage samples was collected from 50 stables in a matched case-control study, where each stable housed one pair consisting of one case and one control horse. Horses in each pair were fed the same haylage and were housed in the same stable. The horse owners were requested to complete a survey with questions regarding feeding and management of the horses. The forage used in each stable was sampled at three occasions during the same winter and analysed for its chemical and microbial composition. The results didn’t show any differences in amount of kg DM per 100 kg BW/day of forage or concentrates between case and control horses. The daily intake of digestible crude protein (dCP), metabolisable energy (MJ MEh), and g neutral detergent fibre (NDF) per 100 kg BW did not differ between case and control horses. The results from this study showed that case and control horses were fed similarly, but does not rule out other nutritional causes of FFL. Further studies on causes of FFL are of interest.